2004
DOI: 10.1086/379695
|View full text |Cite
|
Sign up to set email alerts
|

“Tertiary Dinosaurs” in the Nanxiong Basin, Southern China, Are Reworked from the Cretaceous

Abstract: The Nanxiong and Shanghu Formations of southeastern China span the KT boundary interval and preserve an important paleontological record. A 1285-m section across the KT boundary was measured, and lithological units were documented and sampled. Strata were deposited in alluvial fan/playa mudflat environments in a highly seasonal, semiarid climate. Previous workers placed the KT boundary at the Nanxiong/Shanghu formational contact. The uppermost Nanxiong and lowermost Shanghu Formations contain an assemblage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Examples of deposits that contain similarly high concentrations of vertebrate microfossils are the Upper Cretaceous Conor's Microsite, a siltstone‐rich crevasse‐splay deposit with clay clasts (Wilson, ); and fine‐grained microsite deposits from the Upper Cretaceous Judith River Formation with bivalves, interpreted as autochthonous pond/lake deposits (Rogers & Brady, ). Clay‐pebble conglomerates with 2 mm to 8 cm sized clasts composed of sand and granule sized mud aggregates from the Cretaceous–Tertiary of the Nanxiong Basin, Southern China, are interpreted as distal sheetfloods (Buck et al ., ). These deposits may be similar to the discontinuous conglomerates of the Ballagan Formation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Examples of deposits that contain similarly high concentrations of vertebrate microfossils are the Upper Cretaceous Conor's Microsite, a siltstone‐rich crevasse‐splay deposit with clay clasts (Wilson, ); and fine‐grained microsite deposits from the Upper Cretaceous Judith River Formation with bivalves, interpreted as autochthonous pond/lake deposits (Rogers & Brady, ). Clay‐pebble conglomerates with 2 mm to 8 cm sized clasts composed of sand and granule sized mud aggregates from the Cretaceous–Tertiary of the Nanxiong Basin, Southern China, are interpreted as distal sheetfloods (Buck et al ., ). These deposits may be similar to the discontinuous conglomerates of the Ballagan Formation.…”
Section: Discussionmentioning
confidence: 97%
“…Microsites (concentrations of disarticulated vertebrate microfossils where 75% of vertebrate skeletal elements are ≤5 cm in size), specifically those which occur in fine‐grained sediments (Wilson, ; Rogers & Brady, ), may be similar deposits, although their detailed sedimentology has not been examined. Other similar deposits are mud aggregates (sand grain‐sized clay aggregates: Rust & Nanson, ) and clay–pebble conglomerates (Buck et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This interpretation (the "Stets placement") implies the survival of dinosaurs into the Paleogene and thus argues against a globally synchronized mass extinction coincident with an impact event. Later, Buck et al (2004) accepted the Stets placement but argued that the dinosaur remains above that level were reworked because of debris flows in the upper Pingling Formation (their "Nanxiong Formation") and the lower Shanghu Formation. Taylor et al (2006) reviewed the entire suite of evidence and concluded that the preponderance of evidence supports the Zhao placement.…”
Section: Previous Researchmentioning
confidence: 99%
“…The dating errors were almost always due to reworked fossils, material that had recently experienced time-averaging across the Cretaceous-Paleogene boundary. Such instances are known from France (Buffetaut et al, 1980), China (Buck et al, 2002), and the western interior of North America (Argast et al, 1987;Lofgren, 1995;Renne and Goodwin, 2014). Basal Danian, that is post-Cretaceous, nonavian theropod bones have been reported from the Chatham Islands, New Zealand (Stilwell et al, 2006;Stilwell and Håkansson, 2012).…”
Section: Eocene Dinosaurs In Patagoniamentioning
confidence: 99%